Status and influencing factors of falls among the elderly in a community in Beijing (北京市某社区老年人跌倒现况及其影响因素研究) - ZHAO Dan (赵丹); QI XiaoJiu (齐晓玖); WEN Meng (温萌); GUO Hong (郭红) (中西医结合护理, 2022)
Objective To investigate the status and influencing factors of falls among the elderly in a community in Beijing, and provide reference for the prevention of falls in community. Methods Convenience sampling method was used to investigate 509 elderly residents over 60 years old in a community in Beijing, and logistic regression was used to analyze the risk factors of falls. Results The fall rate of the elderly in the community of Beijing was 26. 72%(136/509). Logistic regression results showed that age(OR=1. 93), abnormal gait(OR=6. 44), abnormal balance(OR=11. 20), urinary/stool incontinence(OR=4. 57), dizziness and vertigo(OR-2. 27), visual impairment(OR=1. 97), history of stroke(OR=3. 02) and arrhythmia(OR=2. 77) were the risk factors for falling of the elderly in the community. Conclusion The fall rate of the elderly in this community in Beijing is high, so the elderly with advanced age, abnormal gait, abnormal balance, urinary/fecal incontinence, dizziness, dizziness, visual impairment, stroke history, arrhythmia should be strengthened to reduce the fall rate of the elderly and the adverse consequences of falling, improve the quality of life of the elderly. (目的 调查北京社区老年人跌倒现状, 并探讨其影响因素, 为社区跌倒预防工作提供参考依据。方法 采用便利抽样法, 对509名60岁以上的社区老年居民进行调查, 采用logistic回归分析跌倒的危险因素。结果 北京某社区老年人的跌倒率为26. 72%(136/509), Logistic回归结果显示, 年龄(OR=1. 93)、步态异常(OR=6. 44)、平衡异常(OR=11. 20)、尿/便失禁(OR=4. 57)、头晕眩晕(OR=2. 27)、视力障碍(OR=1. 97)、脑卒中史(OR=3. 02)、心律失常(OR=2. 77)是社区老年人跌倒的危险因素。结论 北京市该社区老年人跌倒率较高, 对于高龄、步态异常、平衡异常、尿/便失禁、头晕眩晕、视力障碍、有脑卒中史、心律失常的老年人应加强防护, 以降低老年人的跌倒率及跌倒后不良后果, 提高老年人的生活质量。)